No evidence of Alzheimer’s disease pathology in mice infected with Toxocara canis - Vosála Ondřej; Šmídová Barbora; Novák Jan; Svoboda Jan; Petrásek Tomáš; Vojtěchová Iveta; Macháček Tomáš (Parasite)
The potential link between the infections and the development of Alzheimer’s disease (AD) has led to speculations about the role of various pathogens in triggering amyloid-β (Aβ) overproduction, possibly leading to AD onset. The globally distributed dog roundworm Toxocara canis was suggested to be a suitable candidate due to neurotropism of the larvae and infection chronicity. This study investigated whether chronic T. canis infection induces AD-like pathology in mice and whether Aβ is toxic to T. canis. BALB/c and APP/PS1 transgenic mice, which overproduce Aβ, were infected with T. canis L3 larvae and monitored for larval burden, Aβ accumulation, and behavioral changes. In vitro tests of recombinant Aβ toxicity against the larvae were also performed. Despite the presence of T. canis larvae in the central nervous system 8 and 16 weeks post-infection, no significant increase in Aβ concentration or AD-related behavioral alterations were observed. Aβ was detected on the surface and within the intestines of T. canis larvae, but in vitro exposure to recombinant Aβ did not affect larval viability or morphology. Our findings suggest that T. canis infection does not trigger AD-like pathology in mice, and Aβ does not act as an antiparasitic agent. This challenges the emerging hypothesis that chronic neurotoxocarosis infections may contribute to AD development.